Multiple-Case Study of U.S. General Aviation Airports for Operational Sustainability. Issue 7 (July 2020) - Gu, Yue; Johnson, Mary E.
Improving operational sustainability may help U.S. general aviation (GA) airports improve overall sustainable development without substantial financial inputs. An exploratory multiple-case study of five GA airports was conducted to explore the current understandings of airport operational sustainability among U.S. GA airports. Based on findings, a new definition of airport operational sustainability for U.S. GA airports was developed. A set of performance metrics for measuring operational sustainability in U.S. GA airports was identified. The new definition may help GA airports to develop sustainable management plans, and may help airports in other categories to expand their sustainability perspectives. The metrics identified in this study may be used to measure progress to the sustainable development, identify problems, and set performance goals or targets for airports.